Medial arterial calcification: JACC state-of-the-art review - Lanzer, Peter; Hannan, Fadil M.; Lanzer, Jan David; Janzen, Jan; Raggi, Paolo; Furniss, Dominic; Schuchardt, Mirjam; Thakker, Rajesh; Fok, Pak-Wing; Sáez Rodríguez, Julio; Millan, Angel; Sato, Yu; et al. (Journal of the American College of Cardiology, 2021)
Medial arterial calcification (MAC) is a chronic systemic vascular disorder distinct from atherosclerosis that is frequently but not always associated with diabetes mellitus, chronic kidney disease, and aging. MAC is also a part of more complex phenotypes in numerous less common diseases. The hallmarks of MAC include disseminated and progressive precipitation of calcium phosphate within the medial layer, a prolonged and clinically silent course, and compromise of hemodynamics associated with chronic limb-threatening ischemia. MAC increases the risk of complications during vascular interventions and mitigates their outcomes. With the exception of rare monogenetic defects affecting adenosine triphosphate metabolism, MAC pathogenesis remains unknown, and causal therapy is not available. Implementation of genetics and omics-based approaches in research recognizing the critical importance of calcium phosphate thermodynamics holds promise to unravel MAC molecular pathogenesis and to provide guidance for therapy. The current state of knowledge concerning MAC is reviewed, and future perspectives are outlined.